A clinical study of preterm labour - Patil, Prachi; Singh, Richa; Gopal, Sriram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: There has been a rising incidence of preterm labour in India. Preterm labour poses greater risks of morbidity and mortality of the preterm neonates. Various factors contribute towards risk of preterm labour and its outcome. Addressing these factors appropriately improves the outcome in pregnant women. Methods: This prospective observational study was conducted in department of obstetrics and gynaecology from the period of July 2017 to July 2018. Results: The present study was in 98 patients admitted in our hospital with preterm labour. Clinical profile of those patients was studied. Statistically significant association was found between administration of antibiotics and tocolysis in prolongation of pregnancy (p value=0.00). There was an association found between gestational age at birth and immediate neonatal outcome (p value=0.00). Preterm labour was more common in multigravidae (62.4%) and women with cervical length less than 3 cm (85.17%). Conclusions: Preterm labour can be expected more commonly in multigravidae, pregnant women with cervical length less than 3 cm and in presence of high-risk factors. Anticipation of preterm labour, judicious use of antibiotics, tocolytics can improve the outcome of preterm labour.